PEMANFAATAN PENCAMPURAN GYPSUM DENGAN KALSIUM OKSIDA SEBAGAI ZAT ADITIF PADA SISTEM PEMBUMIAN - Ni Wayan Dian Puspita Sukma Dewi; I Gusti Ngurah Janardana; Wayan Arta Wijaya (Jurnal SPEKTRUM, 2021)
One of the most influential factors on the grounding system is the type of soil. Each soilhas a different resistivity. So, it is necessary to add media in the form of additives, one of whichis a mixture of gypsum (CaSO4`.2H2O) and Calcium Oxide (CaO). The purpose of this researchwas to obtain the percentage of the mixture and the effectiveness between gypsum(CaSO4.2H2O) and calcium oxide (CaO) to obtain the maximum quantity of water and to decidethe impact of a mixture of gypsum (CaSO4.2H2O) with calcium oxide (CaO) as a medium foradditives. to reduce the resistivity of the soil. The method used in this study is an experimentalresearch method. The results of this study showed that the mixture of gypsum and calciumoxide that was effectively used was a mixture with a ratio of 3 kg of gypsum and 1 kg of calciumoxide and the percentage decreased resistance value was 37.93%